TEMPERATURE HUMIDITY INDEX AND PHYSIOLOGICAL RESPONSES OF LOCAL RABBIT OFFERED DIFFERENT LEVEL OF ENERGY AND PROTEIN FEEDS AND HOUSED IN TWO CAGE SYSTEMS - Nuriyasa, I.M.; Mastika, I.M.; Mahardika, IG; Kasa, I.W (E-Journal of Animal Science Udayana University, 2013)
An experiment was carried out to study temperature humidity index (THI) and physiological responses of local rabbit offered different level of energy and protein feeds and housed in two cage systems.  A split – plot design consisted of two main plot : under ground shelter  and battery housing system and four diets as sub plot with different energy and protein level. The result show that, under ground shelter cage produced lower (P<0.05) THI than the battery cage (26.17 vs. 27.69).  The lower THI in under ground shelter cage than battery cage causing physiological responses better to the rabbits.  Diets with different energy and protein level did not give significant effect on THI, skin temperature and rectal temperature (P>0.05).  It was observed that there is a significant interaction (P<0.05) between cage system and ration on respiration rate.  Diets did not  have any significant effect (P>0.05) on respiration rate  of the rabbit housed under ground shelter cage. But converse was true for battery cage. Diets containing 2800 kcalME/kg and 18,50% crude protein causing significantly higher (P<0.05) respiration rate  than  other diets.  It was concluded that under ground shelter cage give  a better responds than battery cage.  Diets  differing  in energy and protein level did not affect temperature-humidity index. Further,  diets with 2800 kcalME/kg and 18.50% crude protein gave less physiological impact  than  those diets containing 2600 kcalME/kg and 17% crude protein, 2400 kcalME/kg and 15.50% crude protein, 2200 kcalME/kg and 14% crude protein.
Keywords: Domestic Rabbit, Temperature-Humidity Index, Physiological Responses